A Systematic Review and Meta-analysis of the Use of High-Fidelity Simulation in Obstetric Ultrasound. Issue 1 (February 2021) - Dromey, Brian P.; Peebles, Donald M.; Stoyanov, Danail V.
Abstract : Summary Statement: There is little global consensus on how to train, assess, and evaluate skills in obstetric ultrasound. The outcomes of curricula, where present, are often based on the number of clinical cases completed, rather than objective outcomes. The central question in this review is whether simulation enhances training and prepares trainees for clinical practice. A systematic review was conducted of the currently available literature in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Studies considering the use of simulators in training or assessment of sonographers were eligible for inclusion. We conclude that simulation is best used for acquisition of technical skills and image optimization. Best outcomes are observed when simulation augments traditional learning, with a strong focus on specific, objective, and measurable skills. Integrating simulation into training curricula could allow trainees to contribute to clinical service while learning. How skills learned in a simulated environment translate to the clinic is poorly addressed by the literature.